PHOSPHATE BINDER USE AND MORTALITY AMONG HEMODIALYSIS PATIENTS IN THE DOPPS: EVALUATION OF POSSIBLE CONFOUNDING BY NUTRITIONAL STATUS - Lopes, Antonio Alberto (2012)
BACKGROUND: Poor nutritional status and both hyperphosphatemia and hypophosphatemia are associated with increased mortality in maintenance hemodialysis (MHD) patients. We assessed associations of PB prescription with survival and indicators of nutritional status among (MHD) patients. STUDY DESIGN: Prospective cohort study (DOPPS) 1996 to 2008. SETTING AND PARTICIPANTS: 23,898 MHD patients at 923 facilities in 12 countries. PREDICTORS: Patient-level PB prescription; and case-mix-adjusted facility percentage PB prescription using an instrumental-variable analysis. OUTCOME: All-cause mortality. RESULTS: Overall, 88% of patients were prescribed PBs. The distributions of age, comorbidities and other characteristics showed small differences between facilities with higher and lower percentage PB prescription. Patient-level PB prescription was strongly associated at baseline with indicators of better nutrition, i.e., higher serum creatinine, albumin, normalized protein-catabolic rate, BMI and absence of cachectic appearance. Overall, patients prescribed PBs displayed 25% lower mortality (hazard ratio [HR] = 0.75, 95% confidence interval [CI] = 0.68–0.83) when adjusted for serum phosphorus and other covariates; further adjustment for nutritional indicators attenuated this association (HR = 0.88, 95% CI = 0.80–0.97). This inverse association, however, was observed only for patients with serum phosphorus ≥3.5mg/dL. In the instrumental-variable analysis, case-mix-adjusted facility percentage PB prescription (range: 23–100%) was positively associated with better nutritional status and inversely associated with mortality (HR for 10% more PB = 0.93, 95% CI = 0.89–0.96). Further adjustment for nutritional indicators reduced this association to HR = 0.95 (95% CI = 0.92–0.99). LIMITATIONS: Results were based on PB prescription; PB and nutritional data were cross-sectional; dietary restriction was not assessed; observational design limits causal inference due to possible residual confounding. CONCLUSIONS: Longer survival and better nutritional status were observed for MHD patients prescribed PBs and in facilities with greater percentage PB prescription. Understanding the mechanisms for explaining this effect and ruling out possible residual confounding require additional research.